2021
DOI: 10.14218/jcth.2021.00176
|View full text |Cite
|
Sign up to set email alerts
|

Persistently Rising Alpha-fetoprotein in the Diagnosis of Hepatocellular Carcinoma: A Review

Abstract: Hepatocellular carcinoma (HCC), one of the most common malignant tumors worldwide, is known for its grim prognosis, with untreated life expectancy being only a matter of months after the diagnosis. The difficulty in making a diagnosis early is one of the main contributing factors to the poor prognosis. Alpha-fetoprotein (AFP) had long been used as a surveillance tool, but suboptimal specificity and sensitivity has prompted liver societies to abandon the recommendation for its universal use, even in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
(80 reference statements)
0
19
0
Order By: Relevance
“…AFP, an oncofetal glycoprotein discovered decades ago, has also been used as a serum and gene expression marker to evaluate hepatocyte regeneration activity closely related to concurrent hepatic necroinflammation or damage predisposing the liver to progression to advanced fibrosis, cirrhosis, or HCC [ 34 ]. Growing evidence has revealed that mildly elevated AFP levels (<150 ng/mL) might reflect the status of liver regeneration and damage [ 35 , 36 ]. AFP may be used as an additional predictor of post-SVR LREs to enhance the performance of predictive models for liver-related pathogenesis, which may not be explained by liver fibrosis or its surrogate markers alone [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…AFP, an oncofetal glycoprotein discovered decades ago, has also been used as a serum and gene expression marker to evaluate hepatocyte regeneration activity closely related to concurrent hepatic necroinflammation or damage predisposing the liver to progression to advanced fibrosis, cirrhosis, or HCC [ 34 ]. Growing evidence has revealed that mildly elevated AFP levels (<150 ng/mL) might reflect the status of liver regeneration and damage [ 35 , 36 ]. AFP may be used as an additional predictor of post-SVR LREs to enhance the performance of predictive models for liver-related pathogenesis, which may not be explained by liver fibrosis or its surrogate markers alone [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The core of this criticism is that Serum AFP levels are normal in 30-40% of patients with HCC, with good specificity AFP lacks sensitivity as it is also released by the normal liver in the set of the inflammatory process and hepatocyte damage and most of HCCs develop in cases of long-standing liver disease, to distinguish HCC from background liver pathology as hepatitis requires a high diagnostic cut-off level of AFP about 400-500 ng/mL range. Thus, many HCCs did not achieve these diagnostic levels until the late stages which magnitude the burden of HCC (7) .…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…The clinical utility of AFP has been recently reviewed. [25][26][27][28] Glypican-3 (GPC3), as a member of the proteoglycan family, is a promising therapeutic target and biomarker for the diagnosis and prognosis of HCC. Further discussion of the clinical value of GPC3 in HCC can be found in several reviews.…”
Section: Introductionmentioning
confidence: 99%